CRITICAL REVIEW OF ORGANIZATIONAL AND PERSONALITY EFFECTS ON MANAGER’S JOB STRESS: IS IT DIFFERENT FOR MALAYSIAN MEN AND WOMEN? (Fokus Ekonomi, 2010)
The researches of job stress are pioneered by a classic study by Friedman, Rosenman, and Caroll in 1958. The basic assumption about job stress that is, certain work characteristics are stressor that lead to both personal and organization. Some studies have investigated this job stress in developing countries. Based on the study of Nasrurdin, dkk (2004), it is chosen intentionally, first, to be criticized in endeavor to comprehend the job-related stress experienced by employees in developing countries setting, the second, the study is issued in Indonesian international journal. The main weakness of this study is related to its model. This study focused on personality variables and job stress. This will become problematic because personality is a dispositional variable which is permanent, whereas job stress is a situational variable which is temporary. Those can reflect individual responses toward certain situation. Therefore, personality variable is considered as moderating variable which is positioned as an independent variable because the variance will likely to be low, whereas the variance of job stress is expected to be high.  The proposed model and chosen variable are not based on a certain theory